ANALISIS BUDAYA ORGANISASI TERKAIT VISI MISI RUMAH SAKIT UMUM DAERAH (RSUD) TUAN RONDAHAIM KABUPATEN SIMALUNGUN TAHUN 2020 - Siagian, Ruth Imelda (Jurnal Kajian Kesehatan Masyarakat, 2021)
The presentation of cultural and organizational understanding as stated earlier certainly just not necessarily can be put together just like that. However, it can be seen the essence of each term that forms the understanding of organizational culture. The purpose of this study was to analyze the Organizational Culture related to the Vision and Mission of the Tuan Rondahaim Hospital The type of research used is descriptive qualitative research using the case study method. Taking informants in this study using purposive sampling technique with a homogeneous sampling approach. conducted in-depth interviews with 5 informants consisting of Director, Head of Yanmed, Head of Supporting Facilities, Head of Nursing, and Head of Finance. Also 1 FGD group consisting of 1 representing Room 1 & 2, 1 person representing the VIP Room, 1 Class 3 person, 1 child and perintanology room, 1 IGD, 1 ICU person, and 1 Poli. in general the organizational culture has been implemented as a whole where all employees feel comfortable working because in RSUD Tuan Rondahaim a family atmosphere has been created and the organizational culture that has been implemented has also been adjusted to support the vision and mission of RSUD Tuan Rondahaim but in the process of implementing this organizational culture is still not effective, because some employees are still working not in accordance with their duties and duties and are not disciplined in attendance where there are also employees not yet consistent with the briefing and finger print.